Analysis of the Implementation of PSAK No. 2 in Healthcare Sector Companies in 2021-2022 - Alfayed, Jonathan Tristan; Wahyuni, Nabillah Nur; Anastasia, Anastasia; Simon, Febryanti (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
The cash flow statement is an integral part of the company's financial statements in each period. This indicates that the statement of cash flows is significant, especially in helping users of financial statements in decision-making. Therefore, the company must be able to prepare a cash flow statement following the provisions set by PSAK No. 2 which regulates the cash flow statement. This study aims to identify the cash flow statement of each healthcare sector company in 2021-2022 and its application following the provisions of PSAK No. 2. This study uses a descriptive qualitative method using purposive sampling techniques to collect secondary data that has been published by the IDX official website related to healthcare sector companies listed on the Indonesia Stock Exchange during the 2021-2022 period. The results of the research that has been conducted show that healthcare sector companies have implemented cash flow statements following the provisions stipulated by PSAK No. 2, but it is known that there are still several elements in the company's cash flow statement that do not follow the provisions specified by PSAK No. 2.